2009
DOI: 10.1111/j.1467-8721.2009.01645.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control

Abstract: To successfully pursue a goal in the face of temptation, an individual must first identify that she faces a self-control conflict. Only then will the individual exercise self-control to promote goal pursuit over indulging in temptation. We propose a new model that distinguishes between the problems of conflict identification and those of conflict resolution. We then review research on the factors that influence conflict identification and those that determine conflict resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(65 citation statements)
references
References 19 publications
3
60
1
Order By: Relevance
“…Whereas the resolution of this dilemma ultimately contributes to either short-term benefit or long-term reward, the very way in which the dilemma is handled may involve several options, including the inhibition of an undesired behaviour (e.g., not eating fatty foods), the initiation of a desired behaviour (e.g., eating sufficient fruits and vegetables), or a combination of both. In conceptualising self-control this way we align with important theoretical contributions to the self-control literature, arguing that the very experience of a dilemma instigates self-control efforts (e.g., Fujita, 2011;Hofmann, Baumeister, Förster, & Vohs, 2012;Myrseth & Fishbach, 2009). Indeed, for the most part the self-control literature explicitly stipulates that inhibition of unwanted responses always takes places in view of a more rewarding long-term goal (rather than inhibition per se; cf.…”
mentioning
confidence: 73%
“…Whereas the resolution of this dilemma ultimately contributes to either short-term benefit or long-term reward, the very way in which the dilemma is handled may involve several options, including the inhibition of an undesired behaviour (e.g., not eating fatty foods), the initiation of a desired behaviour (e.g., eating sufficient fruits and vegetables), or a combination of both. In conceptualising self-control this way we align with important theoretical contributions to the self-control literature, arguing that the very experience of a dilemma instigates self-control efforts (e.g., Fujita, 2011;Hofmann, Baumeister, Förster, & Vohs, 2012;Myrseth & Fishbach, 2009). Indeed, for the most part the self-control literature explicitly stipulates that inhibition of unwanted responses always takes places in view of a more rewarding long-term goal (rather than inhibition per se; cf.…”
mentioning
confidence: 73%
“…"), but also that they compare ongoing behavior or the current status of the outcome to that goal (e.g., "where do I currently stand with respect to this goal?"). Monitoring goal progress serves to identify discrepancies between the current and desired state, which enables people to decide how best to allocate effort among salient goals (Carver & Scheier, 1982;Louro et al, 2007), and when and how to exercise restraint or initiate corrective Progress monitoring and goal attainment 33 action (Fishbach et al, 2012;Myrseth & Fishbach, 2009). In light of the present review, we contend that models concerned with specifying the determinants of intentions such as the Theory of Planned Behavior might profitably be extended to integrate the important role of monitoring goal progress.…”
Section: Discussionmentioning
confidence: 99%
“…Progress monitoring should promote goal attainment because it serves to identify discrepancies between the current state and the desired state, and thus enables people to recognize when additional effort or self-control is needed (Fishbach, Touré-Tillery, Carter, & Sheldon, 2012;Myrseth & Fishbach, 2009). For example, dieters who monitor their intake of calories can better decide whether they should allow themselves to have an extra helping of food.…”
mentioning
confidence: 99%
“…To date, studies that used SMS for reminding individuals to monitor RMC have not been conducted. Selfmonitoring of RMC, using a daily food diary, could decrease this consumption because it could help to identify any discrepancies between current and desired levels of consumption (Fishbach et al, 2012;Myrseth & Fishbach, 2009). Specifically, Michie et al (2009) reported that interventions that combined self-monitoring with other behavioural change techniques were significantly more effective than the other interventions for health behaviours.…”
Section: Intervention For Reducing Meat Intakementioning
confidence: 99%